Deviant calvinism : broadening reformed theology - Crisp, Oliver (Fortress Press ; [publisher not identified], 2014)
Deviant Calvinism seeks to show that the Reformed tradition is much broader and more variegated than is often thought. Crisp's work focuses on a cluster of theological issues concerning the scope of salvation and shows that there are important ways in which current theological discussion of these topics can be usefully resourced by attention to theologians of the past. This book contributes to theological retrieval within the Reformed theology, and establishes a wider path to thinking Calvinism differently.